Longitudinal wastewater-based surveillance of vancomycin-resistant Enterococci in tertiary-care hospitals - Emily Au; Nicole Acosta; Barbara J. Waddell; Jangwoo Lee; Kristine Du; R. Benson Weyant; Maria Bautista; Janine McCalder; Jennifer Van Doorn; Kashtin Low; September Stefani; Gail Visser; et al. (Science of The Total Environment, 2026)

Long-term shifts in the spatial distribution of Common Cranes Grus grus - Morgane Gicquel; Lovisa Nilsson; Juan C. Alonso; Matthew Low; Javier A. Alonso; Dmitrijs Boiko; Damon Bridge; Patrick Dulau; Thomas Heinicke; Anne Kettner; Yosef Kiat; Petras Kurlavičius; et al. (Journal of Ornithology, 2026)
Migratory bird distributions are inherently dynamic and vary with seasons, but are also increasingly influenced by climate and land-use changes. Understanding these shifts is crucial for interpreting ecosystem dynamics and guiding future conservation efforts. In this study, we analysed 187,779 resightings (1985–2021) of 5,120 colour-banded Common Cranes ( Grus grus ), originating from 8 northern European countries, to examine long-term spatiotemporal distribution dynamics along the Western and Central European flyways. Our results show that the flyway use has remained largely consistent with the previous studies: most cranes follow the Western European flyway, wintering in France and Spain, whilst a smaller proportion follow the Central European flyway, wintering in Hungary and occasionally reaching Israel and North Africa. However, we also observed a pronounced northward shift in wintering distribution over the past 4 decades. At the same time, breeding distributions showed a slight southward expansion, potentially reflecting both population growth and changes in marking effort. Our results demonstrate the importance of long-term monitoring in detecting range shifts and highlight the need for adaptive conservation planning in the face of accelerating climate and land-use change.

Correction to: The diversity and nesting preferences of birds along an urban-rural gradient in the Kathmandu Valley, Nepal - Dinesh Bhusal; Prashant Ghimire; Matthew Low; Zuzanna M. Rosin; Yajna Prasad Timilsina (Urban Ecosystems, 2025)

The diversity and nesting preferences of birds along an urban-rural gradient in the Kathmandu Valley, Nepal - Dinesh Bhusal; Prashant Ghimire; Matthew Low; Zuzanna M. Rosin; Yajna Prasad Timilsina (Urban Ecosystems, 2025)

Americans’ support for climate justice - Jennifer P. Carman; Danning Lu; Matthew Ballew; Joshua Low; Marija Verner; Seth A. Rosenthal; Kristin Barendregt-Ludwig; Gerald Torres; Michel Gelobter; Kate McKenney; Irene Burga; Mark Magaña; et al. (Environmental Science & Policy, 2025)

A global database of soil seed bank richness, density, and abundance - Alistair G. Auffret; Emma Ladouceur; Natalie S. Haussmann; Eirini Daouti; Tatiana G. Elumeeva; Ineta Kačergytė; Jonas Knape; Dorota Kotowska; Matthew Low; Vladimir G. Onipchenko; Matthieu Paquet; Diana Rubene; et al. (Ecology, 2024)
A soil seed bank is the collective name for viable seeds that are stored naturally in the soil. At the species or population level, the ability to form a seed bank represents a strategy for (re)colonization following a disturbance or other change in the local environmental conditions. At the community level, seed banks are thought to buffer local diversity during periods of environmental change and are often studied in relation to the potential for passive habitat restoration. The role that seed banks play in plant population and community dynamics, as well as their importance in the agricultural sector, means that they have been widely studied in ecological research. This database is the result of a comprehensive literature search, including all seed bank studies from the Web of Science from which data could be extracted, as well as an additional search of the Russian language literature. The database contains information on the species richness, seed density, and/or seed abundance in 3096 records from at least 1929 locations across the world's seven continents, extracted from 1442 studies published between 1940 and 2020. Records are grouped into five broad habitat categories (aquatic, arable, forest, grassland—including shrubland—and wetland), including information relating to habitat degradation from, or restoration to other habitats (total 14 combinations). Sampling protocols were also extracted for each record, and the database was extensively checked for errors. The location of each record was then used to extract summary climate data and biome classification from external published databases. The database has several potential uses. The large geographical spread relative to many other global biodiversity datasets is relevant for investigating patterns of diversity in biogeographical or macroecological contexts. Habitat type and status (intact, degraded, and restored) can be used to provide insights for biodiversity conservation, while the potential effects of sampling method and effort can be used to inform optimized data collection for future seed bank studies. This database is released under the CC‐BY license.

Efficacy of novel anticoagulants derived from tick saliva in preventing hypercoagulation among post-acute COVID-19 patients - Dan Liao; Aaron Wei Liang Li; Cinthia Wan Ting Phua; Cheryl Xue Pei Chuah; Xiao Xun Yang; Tammy Xin Tian Low; Matthew Benson; Shoumo Bhattacharya; R. Manjunatha Kini; Mark Yan Yee Chan; Cho Yeow Koh (Toxicon, 2024)

Nesting habitat suitability and breeding of Asian woollyneck (Ciconia episcopus) in Nepal - Prashant Ghimire; Saroj Panthi; Krishna Prasad Bhusal; Matthew Low; Nabin Pandey; Rojina Ghimire; Bhuwan Singh Bist; Sujan Khanal; Laxman Prasad Poudyal (Ornithology Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Increasing risks for emerging infectious diseases within a rapidly changing High Asia - Charudutt Mishra; Gustaf Samelius; Munib Khanyari; Prashanth Nuggehalli Srinivas; Matthew Low; Carol Esson; Suri Venkatachalam; Örjan Johansson (Ambio, 2022)
The cold and arid mountains and plateaus of High Asia, inhabited by a relatively sparse human population, a high density of livestock, and wildlife such as the iconic snow leopard Panthera uncia , are usually considered low risk for disease outbreaks. However, based on current knowledge about drivers of disease emergence, we show that High Asia is rapidly developing conditions that favor increased emergence of infectious diseases and zoonoses. This is because of the existing prevalence of potentially serious pathogens in the system; intensifying environmental degradation; rapid changes in local ecological, socio-ecological, and socio-economic factors; and global risk intensifiers such as climate change and globalization. To better understand and manage the risks posed by diseases to humans, livestock, and wildlife, there is an urgent need for establishing a disease surveillance system and improving human and animal health care. Public health must be integrated with conservation programs, more ecologically sustainable development efforts and long-term disease surveillance.

Trends in seabird breeding populations across the Great Barrier Reef - Bradley K. Woodworth; Richard A. Fuller; Graham Hemson; Andrew McDougall; Bradley C. Congdon; Matthew Low (Conservation Biology, 2021)
The Great Barrier Reef is an iconic ecosystem, known globally for its rich marine biodiversity that includes many thousands of tropical breeding seabirds. Despite indications of localized declines in some seabird species from as early as the mid‐1990s, trends in seabird populations across the reef have never been quantified. With a long history of human impact and ongoing environmental change, seabirds are likely sentinels in this important ecosystem. Using 4 decades of monitoring data, we estimated site‐specific trends for 9 seabird species from 32 islands and cays across the reef. Trends varied markedly among species and sites, but probable declines occurred at 45% of the 86 species‐by‐site combinations analyzed compared with increases at 14%. For 5 species, we combined site‐specific trends into a multisite trend in scaled abundance, which revealed probable declines of Common Noddy (Anous stolidus), Sooty Tern (Onychoprion fuscatus), and Masked Booby (Sula dactylatra), but no long‐term changes in the 2 most widely distributed species, Greater Crested Tern (Thalasseus bergii) and Brown Booby (Sula leucogaster). For Brown Booby, long‐term stability largely resulted from increases at a single large colony on East Fairfax Island that offset declines at most other sites. Although growth of the Brown Booby population on East Fairfax points to the likely success of habitat restoration on the island, it also highlights a general vulnerability wherein large numbers of some species are concentrated at a small number of key sites. Identifying drivers of variation in population change across species and sites while ensuring long‐term protection of key sites will be essential to securing the future of seabirds on the reef.

The timing of breeding and independence for snow leopard females and their cubs - Örjan Johansson; Giorgia Ausilio; Matthew Low; Purevjav Lkhagvajav; Byron Weckworth; Koustubh Sharma (Mammalian Biology, 2021)
Significant knowledge gaps persist on snow leopard demography and reproductive behavior. From a GPS-collared population in Mongolia, we estimated the timing of mating, parturition and independence. Based on three mother–cub pairs, we describe the separation phase of the cub from its mother as it gains independence. Snow leopards mated from January–March and gave birth from April–June. Cubs remained with their mother until their second winter (20–22 months of age) when cubs started showing movements away from their mother for days at a time. This initiation of independence appeared to coincide with their mother mating with the territorial male. Two female cubs remained in their mothers’ territory for several months after initial separation, whereas the male cub quickly dispersed. By comparing the relationship between body size and age of independence across 11 solitary, medium-to-large felid species, it was clear that snow leopards have a delayed timing of separation compared to other species. We suggest this may be related to their mating behavior and the difficulty of the habitat and prey capture for juvenile snow leopards. Our results, while limited, provide empirical estimates for understanding snow leopard ecology and for parameterizing population models.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Disentangling the effects of date, individual, and territory quality on the seasonal decline in fitness - Tomas Pärt; Jonas Knape; Matthew Low; Meit Öberg; Debora Arlt (Ecology, 2017)
The seasonal timing of reproduction is a major fitness factor in many organisms. Commonly, individual fitness declines with time in the breeding season. We investigated three suggested but rarely tested hypotheses for this seasonal fitness decline: (1) time per se (date hypothesis), (2) late breeders are of lower quality than early ones (individual quality hypothesis), and (3) late breeders are breeding at poorer territories than early breeders (territory quality hypothesis). We used Bayesian variance component analyses to examine reproductive output (breeding success, number fledged, and number of recruits) from repeated observations of female Northern Wheatears ( Oenanthe oenanthe ) and individual territories from a 20‐yr population study. The major part of the observed seasonal decline in reproductive output seemed to be driven by date‐related effects, whereas female age and territory type (i.e., known indicators of temporary quality) contributed to a smaller degree. Other, persistent effects linked to individual and territory identity did not show any clear patterns on the seasonal decline in reproductive output. To better disentangle the quality effects (persistent and temporary) of individual and territory from effects caused by the deterioration of the environment we suggest a protocol combining experimental manipulation of breeding time with a variance–covariance partitioning method used here.

Reproductive patterns result from age‐related sensitivity to resources and reproductive costs in a mammalian carnivore - Geir Rune Rauset; Matthew Low; Jens Persson (Ecology, 2015)
Although the effects of individual age, resource availability, and reproductive costs have been extensively studied to understand the causes of variation in reproductive output, there are almost no studies showing how these factors interact in explaining this variation. To examine this interaction, we used longitudinal demographic data from an 18‐year study of 53 breeding female wolverines ( Gulo gulo ), and corresponding environmental data from their individual home ranges. Females showed a typical age‐related pattern in reproductive output, with an initial increase followed by a senescent decline in later years. This pattern was largely driven by four processes: (1) physiological/behavioral maturation between ages two and three; (2) age‐related differences in the costs of reproduction resulting in an initial increase, and then a declining probability of breeding two years in a row as individuals aged; (3) resource availability (reindeer [ Rangifer tarandus ] carcass abundance; mostly Eurasian lynx [ Lynx lynx ] kills) in the months preceding parturition, which influenced the probability of having cubs, but only for individuals that had successfully bred in the previous year; and (4) resource availability also influenced the cost of reproduction in an age‐dependent manner, as prime age females that had bred in the previous year were more responsive to resource availability than those at other ages. This study demonstrates that by examining how drivers of reproductive variation interact, we can get a much clearer understanding of the mechanisms responsible for age‐related patterns of reproduction. This has implications not only for general ecological theory, but will also allow better predictions of population responses to environmental changes or management based on a population's age‐structure.

A Bayesian hurdle model for analysis of an insect resistance monitoring database - Matthew G. Falk; Rebecca O’Leary; Manoj Nayak; Patrick Collins; Samantha Low Choy (Environmental and Ecological Statistics, 2015)

Invader traits and community context contribute to the recent invasion success of the macroalga Heterosiphonia japonica on New England rocky reefs - Natalie H. N. Low; Annick Drouin; Christopher J. Marks; Matthew E. S. Bracken (Biological Invasions, 2015)

Decomposing the seasonal fitness decline - Meit Öberg; Tomas Pärt; Debora Arlt; Ane T. Laugen; Matthew Low (Oecologia, 2014)

Malaria infections reinforce competitive asymmetry between two Ficedula flycatchers in a recent contact zone - Katarzyna Kulma; Matthew Low; Staffan Bensch; Anna Qvarnström (Molecular Ecology, 2013)
Parasites may influence the outcome of interspecific competition between closely related host species through lower parasite virulence in the host with which they share the longer evolutionary history. We tested this idea by comparing the prevalence of avian malaria ( H aemosporidia) lineages and their association with survival in pied and collared flycatchers ( F icedula hypoleuca and F . albicollis ) breeding in a recent contact zone on the S wedish island of Ö land. A nested PCR protocol amplifying haemosporidian fragments of mt DNA was used to screen the presence of malaria lineages in 1048 blood samples collected during 6 years. Competitively inferior pied flycatchers had a higher prevalence of blood parasites, including the lineages that were shared between the two flycatcher species. Multistate mark–recapture models revealed a lower survival of infected versus uninfected female pied flycatchers, while no such effects were detected in male pied flycatchers or in collared flycatchers of either sex. Our results show that a comparatively new host, the collared flycatcher, appears to be less susceptible to a local northern European malarial lineage where the collared flycatchers have recently expanded their distribution. Pied flycatchers experience strong reproductive interference from collared flycatchers, and the additional impact of species‐specific blood parasite effects adds to this competitive exclusion. These results support the idea that parasites can strongly influence the outcome of interspecific competition between closely related host species, but that the invading species need not necessarily be more susceptible to local parasites.

The relationship between variable host grouping and functional responses among parasitoids of A ntispila nysaefoliella ( L epidoptera: H eliozelidae) - Candace Low; Sonja J. Scheffer; Matthew L. Lewis; Michael W. Gates (Molecular Ecology, 2012)
Our study investigated the importance of variability in the parasitoid community as a source of selection on host group size using a field population of the tupelo leafminer, A ntispila nysaefoliella Clemens, which specializes on tupelo, N yssa sylvatica M arsh. Larvae were collected from leaves with variable numbers of larvae and screened for parasitism using polymerase chain reaction of mitochondrial cytochrome oxidase I using markers designed specifically for amplifying parasitoid DNA while excluding host DNA . This method of selective PCR was effective for detecting the presence and identifying species of immature stages of three hymenopteran superfamilies: C halcidoidea, I chneumonoidea and P latygastroidea, which represented 83.4%, 16.0% and 0.6% of the total detectable parasitism, respectively. Our resulting sequences were then calibrated with sequences from identified adult parasitoids that had been either reared or field‐captured. A cluster analysis revealed 10 distinct clades that showed differences in attack patterns with respect to host traits and season. Total parasitism followed an inverse density‐dependent or density‐independent pattern with respect to host density (number per leaf). However, when parasitoid taxa were considered separately, one clade, which could be a cryptic species of P nigalio maculipes C rawford ( C halcidoidea: E ulophidae), was found to increase its per leaf attack rate with host density. Our results suggest that parasitoid community composition and differences among species in their attack strategies can play a large role in determining the adaptive advantage of host grouping.

Realistic losses of rare species disproportionately impact higher trophic levels - Matthew E. S. Bracken; Natalie H. N. Low (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 461–467 Abstract Predicting the consequences of changes in biodiversity requires understanding both species’ susceptibility to extirpation and their functional roles in ecosystems. However, few studies have evaluated the effects of realistic, non‐random biodiversity losses, severely limiting the applicability of biodiversity research to conservation. Here, we removed sessile species from a rocky shore community in a way that deliberately mimicked natural patterns of species loss. We found that the rarest species in the system act from the bottom up to disproportionately impact the diversity and abundance of consumers. Realistic losses of rare species in a diverse assemblage of seaweeds and sessile invertebrates, collectively comprising

Complete chloroform dechlorination by organochlorine respiration and fermentation - Matthew Lee; Adrian Low; Olivier Zemb; Joanna Koenig; Astrid Michaelsen; Mike Manefield (Environmental Microbiology, 2012)
Summary Chloroform (CF, CHCl 3 ) is a recalcitrant and toxic environmental pollutant. In this communication we report for the first time a microbial community capable of complete CF dechlorination by metabolic processes. Cultures derived from subsurface soil (3.5 m) could sustain complete dechlorination of CF at levels of least 360 µM at a rate of 40 µM per day. Scrutiny of CF dechlorination revealed two metabolic processes at work. First, CF was respired to dichloromethane (DCM, CH 2 Cl 2 ), which was then fermented to acetate, hydrogen and carbon dioxide. Elevated hydrogen partial pressures were found to inhibit the fermentation process. Interspecies hydrogen transfer was observed in the form of methanogenesis and acetogenesis. This suggests that the dechlorination process required syntrophic partners to maintain low hydrogen partial pressures. 13 C‐labelled DCM was employed to help elucidate the chemistry of the process and identify bacterial community members involved. CF respiring cultures, where emulsified vegetable oil was supplied as the electron donor and DCM fermenting cultures, where DCM was supplied as the sole organic carbon source were studied separately. Pyrosequencing of these cultures revealed Dehalobacter lineages as a predominant community member in both. Subsequent growth experiments confirmed that the proliferation of Dehalobacter was linked directly to both the dehalorespiration and dehalofermentation processes.

The persistence of the snow petrel (Pagodroma nivea) in Dronning Maud Land (Antarctica) for over 37,000 years - Göran Thor; Matthew Low (Polar Biology, 2011)

Daily patterns of nest visits are correlated with ambient temperature in the Northern Wheatear - Matthew Low; Sönke Eggers; Debora Arlt; Tomas Pärt (Journal of Ornithology, 2008)

Experimental evaluation of a new ground-based survey method for estimating the density and abundance of nesting Adélie penguins Pygoscelis adeliae - Matthew Low; Lisa Meyer; Colin Southwell (Polar Biology, 2008)

Cloacal erection promotes vent apposition during forced copulation in the New Zealand stitchbird (hihi): implications for copulation efficiency in other species - Matthew Low; Isabel Castro; Åsa Berggren (Behavioral Ecology and Sociobiology, 2005)